Percutaneous Coronary Intervention In octogerians compared with very young Patients - Ahmed Neama Rgeeb (Kufa Journal for Nursing Sciences)
Introduction: Still percutaneous coronary intervention (PCI) in elderly people challenging for the interventionist as complications and comorbidities are frequent in them.